Effect of advancing age on inter-frequency amplitude ratio of ocular vestibular evoked myogenic potentials. (1st December 2021) - Singh, Niraj Kumar; Firdose, Husna; Barman, Animesh
Abstract: Objective: The inter-frequency amplitude ratio (IFAR) is the ratio of the amplitude of 1000-Hz tone-burst evoked ocular vestibular evoked myogenic potential (oVEMP) to the 500 Hz tone-burst evoked oVEMP. Since IFAR is an amplitude-based parameter, and the amplitudes of oVEMP for different frequencies are differentially affected by ageing, IFAR could potentially be affected by the ageing process. Therefore, we aimed to examine the effects of ageing on the IFAR of oVEMPs. Design: Multiple static groups comparison. Study sample: We recorded oVEMPs for 500 Hz and 1000 Hz tone-bursts from 270 healthy individuals, each included in one of the six age groups. Results: The IFAR was significantly larger in the ≥60 years age group than the age groups up to 49 years. Furthermore, the IFAR in the 50–59 years age group was significantly larger than all the other age groups up to 39 years. There was a significant positive correlation between age and IFARs ( p  < 0.01). Conclusions: IFAR, a sensitive tool in the test battery for the diagnosis of Meniere's disease, is affected even in healthy individuals due to ageing; hence its cautious interpretation is recommended when evaluating adults >50 years of age who are suspected of having Meniere's disease.